Stage-specific differences in the requirements for germline stem cell maintenance in the Drosophila ovary. - Shcherbata, H.R.; Ward, E.J.; Fischer, K.A.; Yu, J.Y.; Reynolds, S.H.; Chen, C.H.; Xu, P.; Hay, B.A.; Ruohola-Baker, H. (Cell Stem Cell, 2007)
In this study, we uncover a role for microRNAs in Drosophila germline stem cell (GSC) maintenance. Disruption of Dicer-1 function in GSCs during adult life results in GSC loss. Surprisingly, however, loss of Dicer-1 during development does not result in a GSC maintenance defect, although a defect is seen if both Dicer-1 and Dicer-2 function are disrupted. Loss of the bantam microRNA mimics the Dicer-1 maintenance defect when induced in adult GSCs, suggesting that bantam plays a key role in GSC self-renewal. Mad, a component of the TGF-beta pathway, behaves similarly to Dicer-1: adult GSC maintenance requires Mad if it is lost during adult life, but not if it is lost during pupal development. Overall, these results show stage-specific differential sensitivity of GSC maintenance to certain perturbations, and suggest that there may be Dcr-2 dependent redundancy of GSC maintenance mechanisms during development that is lost in later life.